2016
DOI: 10.3390/rs8050423
|View full text |Cite
|
Sign up to set email alerts
|

MODIS-Based Mapping of Secchi Disk Depth Using a Qualitative Algorithm in the Shallow Arabian Gulf

Abstract: Abstract:Regionally calibrated algorithms for water quality are strongly needed, especially for optically complex waters such as coastal areas in the Arabian Gulf. In this study, a regional qualitative algorithm was proposed to retrieve seawater transparency, with Secchi disk depth (SDD) as a surrogate, in the Arabian Gulf. A two-step process was carried out, first estimating the diffuse attenuation coefficient of downwelling irradiance at 490 nm (K d _490) from MODIS/Aqua imagery and then SDD based on empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…Due to the shallowness and turbulence found in the sampling area, the waters are likely to be turbid, which means that the bottom reflectance issue is likely minimum. Similar patterns have been reported by Al Kaabi et al [8], were the authors demonstrated seasonal variations of Secchi disk depth (SDD) over the entire Gulf using a set of in situ SDD measurements versus 14-year time-series of MODIS/Aqua K d data. Generally, higher SSD values were observed in summer, while lower values were found in winter [8] (Al Kaabi et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Due to the shallowness and turbulence found in the sampling area, the waters are likely to be turbid, which means that the bottom reflectance issue is likely minimum. Similar patterns have been reported by Al Kaabi et al [8], were the authors demonstrated seasonal variations of Secchi disk depth (SDD) over the entire Gulf using a set of in situ SDD measurements versus 14-year time-series of MODIS/Aqua K d data. Generally, higher SSD values were observed in summer, while lower values were found in winter [8] (Al Kaabi et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Similar patterns have been reported by Al Kaabi et al [8], were the authors demonstrated seasonal variations of Secchi disk depth (SDD) over the entire Gulf using a set of in situ SDD measurements versus 14-year time-series of MODIS/Aqua K d data. Generally, higher SSD values were observed in summer, while lower values were found in winter [8] (Al Kaabi et al, 2016). The authors developed a locally-adapted algorithm to estimate SSD from satellite-derived K d over the Gulf using Lee's algorithm [32].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations